A randomised double-blind trial of diltiazem in the treatment of Raynaud's phenomenon. Issue 1 (January 1985) - Kahan, A; Amor, B; Menkes, C J
Abstract : The efficacy of diltiazem in the treatment of Raynaud's phenomenon was assessed in a prospective double-blind randomised cross-over trial in 16 patients (7 progressive systemic sclerosis, 2 rheumatoid arthritis, 1 systemic lupus erythematosus, and 6 idiopathic Raynaud's phenomenon). Each patient received diltiazem 120 mg and placebo three times a day for two weeks. The attack frequency of Raynaud's phenomenon was measured by a diary count; its severity was assessed by means of a 10 cm visual analogue scale with 0 representing minimum and 10 representing maximum severity. Diltiazem significantly decreased the frequency and severity of Raynaud's phenomenon as compared with placebo. This improvement was striking in patients with idiopathic Raynaud's phenomenon but did not reach statistical significance in patients with associated systemic disease. We conclude that diltiazem is effective in the treatment of Raynaud's phenomenon, especially in patients with idiopathic vasospastic disease.